Sustaining forest biodiversity: Exploring the effect of long-term natural disturbance dynamics on contemporary lichen communities in primary forest ecosystems - Rhiannon Gloor; Marek Svitok; Martin Mikoláš; Jeňýk Hofmeister; Josef Halda; Pavel Janda; Francesco Maria Sabatini; Lucie Zemanová; Arne Buechling; Daniel Kozák; Matej Ferenčík; Michal Frankovič; et al. (Forest Ecosystems)
In this era of biodiversity loss and climate change, quantifying the impacts of natural disturbance on forest communities is imperative to improve biodiversity conservation efforts. Epiphytic and epixylic lichens are effective forest quality bioindicators, as they are generally long-lived organisms supported by continuity of specific forest structures and their associated microclimatic features. However, how lichen communities respond to the effects of fluctuating historical disturbances remains unclear. Using a dendrochronological approach, this study investigates how natural disturbance dynamics indirectly influence various lichen community metrics in some of Europe's best-preserved primary mixed-beech forests. Mixed modelling revealed that natural historical disturbance processes have decades-long effects on forest structural attributes, which had both congruent and divergent impacts on lichen community richness and composition. Total species richness indirectly benefited from both historical and recent higher-severity disturbances via increased standing dead tree basal area and canopy openness respectively - likely through the presence of both pioneer and late-successional species associated with these conditions. Red-listed species richness showed a dependence on habitat continuity (old trees), and increased with disturbance-related structures (standing dead trees) whilst simultaneously benefiting from periods without severe disturbance events (old trees and reduced deadwood volume). However, if the disturbance occurred over a century in the past, no substantial effect on forest structure was detected. Therefore, while disturbance-mediated forest structures can promote overall richness, threatened species appear vulnerable to more severe disturbance events – a concern, as disturbances are predicted to intensify with climate change. Additionally, the high number of threatened species found reinforce the critical role of primary forest structural attributes for biodiversity maintenance. Hence, we recommend a landscape-scale conservation approach encompassing forest patches in different successional stages to support diverse lichen communities, and the consideration of long-term disturbance dynamics in forest conservation efforts, as they provide critical insights for safeguarding biodiversity in our changing world.